Regional empowerment within the European framework : regionalist parties’ territory-oriented strategies in the regional, statewide and supranational parliamentary arenas - Strnad, Michal; Druláková, Radka, 1973-; Eberle, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This study addresses the parliamentary dimension of regional empowerment within the context of the European Union (EU). Focusing on regionalist parties as the principal political actors behind the regionalist agenda, it explores whether and how these parties advance territorial objectives in the parliaments they occupy. More specifically, it evaluates the legislation regionalist parties introduce in all direct representation organs within EU multi-level governance to empower the regional territory and community. Manual content analysis is applied to the territorial demands in the legislative proposals submitted by Südtiroler Freiheit, Femu a Corsica, and Plaid Cymry – distinct regionalist parties from different territorial settings – in the regional assemblies, statewide parliaments (lower and upper chamber), and the supranational Committee of the Regions and European Parliament over a recent salient, crisis-ridden period (January 2018 – December 2022). To validate and contextualise their legislative behaviour, a complementary framed thematic analysis is applied to their EU-related interventions in regional assemblies, i.e. on this party family’s core reference level, over the same timeframe. Regionalist parties adopt a proactive, context-sensitive, vertically coherent, and rule-abiding parliamentary strategy for regional empowerment. Proposing territoryoriented legislation on all territorial levels, they sharply differentiate what they demand from whom and where by modifying their territorial demands to fit the changing parliamentary context: Demands for greater self-government, safeguards against competence encroachments, and concrete region-oriented policies are addressed to the state from the regional assemblies and statewide parliaments.
Demands for protecting and promoting ethnic and linguistic minorities, fostering regional development, and strengthening regional involvement in EU policymaking are addressed to the EU from the Committee of the Regions and the European Parliament (as well as the lower territorial levels). Notably, many generalised EU-addressed territorial demands targeting all European regions show clear thematic continuity with individual, specific demands addressed to the state. Portraying the contemporary EU as unwilling to support selfdetermination, regionalist parties reduce it to a protection and development framework, which makes their multi-level legislative behaviour and discourse highly consistent. Based on three cases providing considerable variability along theoretically relevant dimensions, this exploratory comparative study provides evidence that regionalist parties advance territorial objectives through the already available opportunity structures, revealing on which territorial level regional empowerment is initiated, by what means, and with what intensity. It further sheds original light on the capacity of EU multilevel governance to accommodate territorial demands through an orderly, democratic procedure. This significantly contributes to our understanding of regional empowerment within the European framework as practised and experienced in the parliamentary arenas and, by extension, enhances our knowledge about the relationship between regionalism and European integration. Methodologically, it advances past qualitative evaluations by employing two complementary methods original in data extraction, processing, and treatment applied to two corpora of previously unused parliamentary data.
Vedoucí práce: Radka Druláková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor disert. práce]; disertace; dissertations